FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN KONSUMEN SAYURAN KANGKUNG KECAMATAN AMPANA KOTA KABUPATEN TOJO UNA-UNA - Oktaviana, Dwi Astri; Effendy, Effendy; Pratama, Fardhal (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The purpose of this research was to determine the effect of various factors, including the prices of water spinach and long bean (as a substitute good), consumer income, number of family dependents, and consumer tastes on the demand for water spinach. The study was conducted in both the morning and evening markets in Ampana Kota. Multiple Linear Regression was utilized to test the hypotheses in this study. The analysis revealed that the coefficient of determination (R2) was 0.728, indicating a reasonably strong relationship between the variables. The F test results showed that the calculated F value (12.827) was greater than the critical F value (2.758), indicating that the multiple linear regression model is suitable for explaining the effect of the spinach and long bean prices, consumer income, number of family dependents, and consumer age on the demand for water spinach. These factors had simultaneously significant effect on the spinach demand. Separately, all factors had also a significant effect on the demand.